Proceedings of the 4th International Congress of Automotive and Transport Engineering (AMMA 2018) - Burnete, Nicolae; Varga, Bogdan Ovidiu (Proceedings in Automotive Engineering, 2019)
This volume includes selected and reviewed papers from the 4th International Congress of Automotive and Transport Engineering, held in Cluj, Romania, in September 2018. Authors are experts from research, industry and universities coming from 14 countries worldwide. The papers are covering the latest developments in automotive vehicles and environment, advanced transport systems and road traffic, heavy and special vehicles, new materials, manufacturing technologies and logistics, accident research and analysis and innovative solutions for automotive vehicles. The conference is organized by SIAR (Society of Automotive Engineers from Romania) in cooperation with FISITA.